Greece : Second Post-Program Monitoring Discussions-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Greece. (IMF Staff Country Reports; Country Report ;, 2020)
The pandemic interrupted a modest recovery. Following Greece's early and strict containment measures, GDP contracted by 7.9 percent in 2020H1, slightly worse than the Euro Area (EA) unweighted average excluding Luxembourg. A further hit is expected in Q3, the peak of Greece's tourism season. The fiscal response to the pandemic has been wellorganized and has mitigated its impact, while Single Supervisory Mechanism (SSM) accommodation will delay the expected hit on banks, which were already vulnerable pre- COVID-19. In the context of the 2019 Article IV Consultation (November 2019), staff assessed that Greece's public debt is sustainable over the medium-term but its long-term public debt sustainability is not assured under a realistic set of macro-fiscal assumptions.